Association of sarcopenia with mortality and end‐stage renal disease in those with chronic kidney disease: a UK Biobank study. Issue 3 (5th May 2021) - Wilkinson, Thomas J.; Miksza, Joanne; Yates, Thomas; Lightfoot, Courtney J.; Baker, Luke A.; Watson, Emma L.; Zaccardi, Francesco; Smith, Alice C.
Abstract: Background: Sarcopenia, a degenerative and generalized skeletal muscle disorder involving the loss of muscle function and mass, is an under‐recognized problem in clinical practice, particularly in chronic kidney disease (CKD). We aimed to investigate the prevalence of sarcopenia in individuals with CKD, its risk factors, and its association with all‐cause mortality and progression to end‐stage renal disease (ESRD). Methods: UK Biobank participants were grouped according to the presence of CKD (defined as an estimated glomerular filtration rate <60 mL/min/1.73 m 2 ) and as having probable (low handgrip strength), confirmed (plus low muscle mass), and severe sarcopenia (plus poor physical performance) based on the 2019 European Working Group of Sarcopenia in Older People and Foundation for the National Institutes of Health criteria. Risk factors were explored using logistic regression analysis. Survival models were applied to estimate risk of mortality and ESRD. Results: A total of 428 320 participants, of which 8767 individuals with CKD (46% male, aged 62.8 (standard deviation 6.8) years, median estimated glomerular filtration rate 54.5 (interquartile range 49.0–57.7) mL/min/1.72 m 2 ) were included. Probable sarcopenia was present in 9.7% of individuals with CKD compared with 5.0% in those without ( P  < 0.001). Sarcopenia was associated with being older; inflammation; poorer renal function; and lower serum albumin, total testosterone, and haemoglobin. The largest risk factors for sarcopenia were having three or more comorbidities (odds ratio: 2.30; 95% confidence interval: 1.62 to 3.29; P  < 0.001) and physical inactivity: participants in the highest quartile of weekly activity were 43% less likely to have sarcopenia compared to the lowest quartile (odds ratio: 0.57; 0.42 to 0.76; P  < 0.001). Participants with CKD and sarcopenia had a 33% (7% to 66%; P  = 0.011) higher hazard of mortality compared with individuals without. Sarcopenic CKD individuals had a 10 year survival probability of 0.85 (0.82 to 0.88) compared with 0.89 (0.88 to 0.30) in those without sarcopenia, an absolute difference of 4%. Those with sarcopenia were twice as likely to develop ESRD (hazard ratio: 1.98; 1.45 to 2.70; P  < 0.001). Conclusions: Participants with reduced kidney function are at an increased risk of premature mortality. The presence of sarcopenia increases the risk of mortality and ESRD. Appropriate measurement of sarcopenia should be used to identify at‐risk individuals. Interventions such as physical activity should be encouraged to mitigate sarcopenia.